2018
DOI: 10.3390/foods7010008
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Metabolism of Phenolics from Digests of Polyphenol-Rich Potato Extracts Using the Caco-2/HepG2 Co-Culture System

Abstract: The bioactivity of dietary polyphenols depends upon gastrointestinal and hepatic metabolism of secondary microbial phenolic metabolites generated via colonic microbiota-mediated biotransformation. A polyphenol-rich potato extract (PRPE) containing chlorogenic, caffeic, and ferulic acids and rutin was digested in a dynamic multi-reactor gastrointestinal simulator of the human intestinal microbial ecosystem (GI model). Simulated digestion showed extensive degradation of the parent compounds and the generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
(74 reference statements)
0
28
0
Order By: Relevance
“…However, little work has been done to clarify the antitumour effects of CA on kidney cancer. Since CA has been verified through in‐vitro and in‐vivo studies that it is highly bioavailable in humans and protects d ‐galactose‐induced kidney injury, we reasonably speculate that CA may possess antitumour activity against RCC. In this study, we firstly report the inhibition effect of CA against RCC cells and reveal the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 83%
“…However, little work has been done to clarify the antitumour effects of CA on kidney cancer. Since CA has been verified through in‐vitro and in‐vivo studies that it is highly bioavailable in humans and protects d ‐galactose‐induced kidney injury, we reasonably speculate that CA may possess antitumour activity against RCC. In this study, we firstly report the inhibition effect of CA against RCC cells and reveal the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 83%
“…Although such compounds are poorly absorbed [ 22 ], their relatively high concentrations in the gut lumen could exert functional anti-colon cancer effects. There are a limited number of studies regarding the anti-cancer effects of CGA and CA on colon cancer cell lines, including Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that CGA shows many biological properties; it is widely accepted that this molecule has several human health benefits, acting as an antibacterial [ 2 ], anti-inflammatory [ 3 ], and antioxidant [ 4 ] agent, as well having hypoglycemic and hypolipidemic [ 5 ] activities. In addition, in vivo and in vitro studies have shown that CGA is highly bioavailable in humans [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%